GOLD MORTGAGE FINANCING SYARIAHON BANK SYARIAH MANDIRI - henny zurika (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The objective of this tudy was determine how the implementation procedures,assessment of gold pawn syariah and the contribution resulting from the gold pawn bank syariah mariah branch in medan.